A new section, Lactifluus section Neotropicus (Russulaceae), and two new Lactifluus species from the Atlantic Forest, Brazil. Issue 4 (18th May 2020) - Duque Barbosa, Jaime AndrÉs; Delgat, Lynn; Galváo Elias, Samuel; Verbeken, Annemieke; Neves, Maria Alice; Carvalho, Aníbal alves de
Abstract : Lactifluus is a monophyletic genus of ectomycorrhizal fungi with about 200 described species classified in four subgenera: L. subg. Gymnocarpus, L. subg. Lactariopsis, L. subg. Lactifluus, and L. subg. Pseudogymnocarpus . Currently L. subg. Lactariopsis is considered monophyletic with approximately 57 species described and classified in four sections: Albati, Edules, Lactariopsis, and Russulopsidei. There are few species of L. subg. Lactariopsis described from the Neotropical region, however local mycologists commonly collect specimens of this subgenus during their mycological surveys. The goals of the present study are to evaluate the phylogenetic and morphological relationships of the species from L. subg. Lactariopsis found in Brazil, to contribute to the knowledge of Lactifluus in Neotropical ecosystems by describing a new section in this subgenus and two new species from Brazil, and to document L. neotropicus as a new record from Brazil. Based on morphological and phylogenetic evidence we propose Lactifluus sect. Neotropicus as a new section and Lactifluus catarinensis and L. marielleae as two new species in this section. We provide a key to the species of L. sect. Neotropicus, which is shown to be a monophyletic group of Neotropical species within L. subg. Lactariopsis . The most striking characteristic of several species in L. subg. Lactariopsis is the secondary angiocarpic development, not present in the other subgenera. Species with a secondary veil can be found in two lineages that diversified more recently than the rest of the genus: L. sect. Lactariopsis and L. sect. Neotropicus. Species that show morphological affinities with the two new species in L . sect. Neotropicus described here are commonly found and we expect a greater diversity to be revealed of this section in the Neotropical region.